An Analysis of the Christian Belief of Chinese Immigrants in America since the 19th century - ZHANG, Xiaoying (Journal of Research for Christianity in China (JRCC), 2025)
Christianity is the most popular religion in the world, which has great influence on the Western society and the overseas Chinese immigrants living in it. Christianity has occupied the mainstream in the United States. Chinese immigrants have been actively pursued by the church since they set foot in the United States. After spreading for more than half a century, Christianity has become the main religious belief of Chinese Americans.